The effect of a workplace intervention programme on return to work after stroke: a randomised controlled trial. (July 2015) - Ntsiea, MV; Van Aswegen, H; Lord, S; Olorunju S, S
Objective: To determine the effect of a workplace intervention programme on the rate of return to work of previously employed stroke survivors in the Gauteng province of South Africa. Design: A randomised controlled trial. Setting: Participants' workplaces and three hospitals with stroke rehabilitation facilities. Subjects: Eighty stroke survivors between the ages of 18 and 60 years who were employed at the time of stroke onset. Intervention: The workplace intervention programme was tailored according to functional ability and workplace challenges of each stroke survivor. The control group received usual stroke care which took into consideration job requirements but without workplace intervention. Main outcomes: The primary outcome was return to work rate. Secondary outcomes included activities of daily living (ADLs), mobility, basic cognitive function and perceived quality of life. Results: At six months follow-up 60% ( n = 24) of stroke survivors in the intervention group returned to work compared to 20% ( n = 8) in the control group ( P <0.001). The odds ratio for return to work for stroke survivors in the intervention group was 5.2. For every unit increase in the ADLs and cognitive assessment score, the odds of return to work increased by 1.7 and 1.3 respectively; those who returned to work had better quality of life than those who did not return to work ( P = 0.05). Conclusion: A workplace intervention consisting of workability assessments and workplace visits was effective in facilitating return to work for stroke survivors in the Gauteng province of South Africa.